AB1368 Insights from a routine care rheumatoid arthritis registry in turkey (TRAV): A third of rheumatoid arthritis patients are in remission/low disease activity and 1/5 are on biologic agents. (23rd January 2014) - Inanc, N.; Hatemi, G.; Simsek, I.; Can, M.; Tascilar, K.; Ugurlu, S.; Pay, S.; Erdem, H.; Yilmaz, S.; Cinar, M.; Cakir, N.; McCracken, W.A.; et al.
Abstract : Background: New paradigm of early and aggressive approach has led to better outcomes for RA, especially documented from randomized clinical trials (RCT). However, real world applicability of these "treating to target" approaches can only be assessed by routine care registries in different populations, with different populations and drug use. TRAV (Turkish acronym for "Turkish Rheumatoid Arthritis Registry") was established in 2010 with the aim of collecting data on RA patients seen in routine care in Turkey, the first consecutive patients database to do so. Objectives: To describe the current treatment patterns and response of rheumatoid arthritis in Turkey, in a first in Turkey consecutive patients database. Methods: Consecutive patients seen at participating centers complete at each visit a MDHAQ which includes scales for physical function, pain, and patient global. Physicians complete global assessment VAS, in addition to tender and swollen joint counts. RAPID3 (routine assessment of patient index data), DAS28 and CDAI are calculated. Demographics, self-reported disease activity measures, clinical data and medication usage were abstracted from the last visit of individuals with RA. Significant differences in measures were determined using the Kruskal-Wallis test for continuous and ordinal measures and Chi-square test for categorical measures. Results: 896 RA patients were enrolled (mean age 53, disease duration 8.9 years, 82% female, education 6.9 years).There were significant differences between centers in years of disease duration and education. Overall, 21.2% of patients were in remission and 13.2% in low disease activity as measured by RAPID3, with similar percentages when DAS28 and CDAI were compared. Pain levels and function were also found comparable between different centers. 22.5% of patients were on biologic agents, with some variation in use among the different centers, which was also seen for MTX (overall 47%) and prednisone use (overall 40%). Patients on biologic agents (n=200) had significantly worse function compared to patients on only DMARDs (n=696) (2.1 vs 2.5, p=0.002), likely a reflection of the point biologics were considered for use in this population. Conclusions: In this Turkish RA population, 1/3 of the patients were in remission or low disease activity, with one in five overall on biologic agents, a higher number than most European countries. There were also some differences among treatment centers, which may reflect both the types of patients seen and different treatment approaches. However, mean function and composite indices scores were similar among all centers as a result of a routine care registry. These data present an initial look at the current treatment of RA with a treat to target approach in Turkey and will be enhanced with additional patients and longer follow up. Acknowledgements: The authors would like to thanks Cortex for their help with data entry and Bristol-Myers Squibb for an unrestricted grant to support data entry. Disclosure of Interest: N. Inanc: None Declared, G. Hatemi: None Declared, I. Simsek: None Declared, M. Can: None Declared, K. Tascilar: None Declared, S. Ugurlu: None Declared, S. Pay: None Declared, H. Erdem: None Declared, S. Yilmaz: None Declared, M. Cinar: None Declared, N. Cakir: None Declared, W. McCracken: None Declared, C. Swearingen: None Declared, H. Direskeneli: None Declared, Y. Yazici Grant/Research support from: BMS, Centocor, Abbott, Genentech, Celgene, Consultant for: Abbott, BMS, Centocor, Celgene, Pfizer, genentech, UCB, Takeda